RAIL PASSENGERS RIGHTS - Đurđev, Dušanka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Тhe legal framework of rail passengers rights is set out in a combination of international and European law: an international measure, the rather unwieldy Uniform Rules concerning the Contract for International Carriage of Passengers and Luggage by Rail, forming part of theConvention concerning International Carriage by Rail of 9 May 1980 (as amended by theVilnius Protocol of 3 June 1999) [‘CIV’], lays down a basic framework which is then fleshed out by more recent EU legislation, Regulation (EC) No 1371/2007 on Rail Passengers’ Rights and Obligations. Regulation 1371/2007/EC on rail passenger rights and obligations sets out minimum quality standards that have to be guaranteed to all passengers on all lines.